ROAD SEDIMENT PRODUCTION AND DELIVERY IN KHANG NINH COMMUNE, BA BE, BAC KAN - The Doi, Bui; Huy Luan, Hua; MacDonald, Lee; Van Dien, Pham (Journal of Forestry Science and Technology, 2016)
This study used three sediment fences to measure sediment production caused by water from three road segments for over one month in the wet season in Khang Ninh Village, Ba Be, Bac Kan, Vietnam. The mean sediment production rate from native surface roads was 0.6023 kg/m². Comparisons among segments showed that recently-graded native surface roads produced more sediment than ungraded native surface roads and of course the number of sediment production depended on the amount of precipitation, slope segments and other external factors. Sediment production on native surface roads was best predicted by the product of road area times road slope (A*S) (Coe D. 2006.). Road sediment production can be reduced by a variation of rocks and vegetation increasing the frequency of road drainage structures, avoiding locations that generate more road surface and ditch runoff, and minimizing grading and traffic. Sediment delivery was assessed by a survey of 8 road segments along 2 km of a forest road. 819 m of the surveyed 2 km of this road are directly connected to the stream. Gully initiation increased with road segment length, side-slope gradients, road designs that concentrate road runoff and infiltration capacity of the soil. Road sediment delivery can be minimized by the construction of a drain-ditch or reducing the amount of runoff processes on the road surface.